Length of main left coronary artery in relation to atherosclerosis of its branches. A coronary arteriographic study. - Gazetopoulos, N (1976)
The relation between the length of the main left coronary artery and the presence of atherosclerosis in its branches or the presence of complete left bundle-branch block was studied by selective coronary arteriography in 43 persons. The length of the main left coronary artery was found to be significantly shorter in patients with coronary atherosclerosis than in subjects without angiographic evidence of coronary artery disease. In patients with electrocardiographic evidence of complete left bundle-branch block, the length of the left main coronary artery was significantly shorter than that in both previous groups. In view of these findings, it is suggested that a short main left coronary artery should be considered as a congenital factor predisposing to the development of coronary artery disease. The possible mechanisms leading to atherosclerosis of the left coronary arterial branches in the presence of a short main trunk are discussed.